Analysis of Mental Health and Spirituality in Employees of Bank - Amani, Camalia Naura; Mangestuti, Retno; Elfa, Asriana (Psikoislamika: Jurnal Psikologi Islam, 2025)
Abstract: Employees are individuals who work as part of an organization or company. Mental health and spirituality are two important dimensions in an individual's life, especially in the context of a work environment that often creates demands and pressures. This study aims to explore mental health and spirituality in Bank employees. This study uses qualitative methods with observation and interview techniques. Research participants consisted of five employees consisting of Office Boy (OB), Security Guard, Customer Service, Insurance Service, and Marketing Admin. The results showed that the majority of Bank employees had a fairly good level of mental health, marked by a good level of psychological well-being. However, some employees also experience psychological distress, especially related to high job demands. For example, employees have experienced stress when there are demands to work on reports in a short time or when a customer complains. Overall, the level of employee spirituality is also quite good, with many employees reporting positive spiritual practices in their daily lives. This research provides insight into the mental health and spirituality of employees at Bank, and is expected to be the basis for developing more holistic employee welfare programs in this company. Keywords: Mental health; spirituality; employees